OPTIMALISASI POTENSI PETERNAK SUSU SAPI PERAHMELALUI PENYULUHAN DAN PELATIHAN PEMBUATAN KEJUDAN YOGHURT ANEKA RASA GUNA MENINGKATKANPENDAPATAN MASYARAKAT - Himmatul Hasanah, Astuti, Ekosari Roektiningrum, (Universitas Negeri Yogyakarta, 2011)
Program the society devotion in Orchard Ngepring, Purwobinangun,Pakem, Sleman, Special Region this Yogyakarta aim to can make theyoghurt and cheese use the sour bacterium of laktat, can make the sourbacterium starter of laktat for the yoghurt of cheese and, can be non-stopedto make the yoghurt and cheese for the sale of as innovation of milk productafter existence of program PPM.Step of training Activity done by that is first through counselling ofmaking of milk product become the yoghurt and cheese; second give thetraining make the cheese and yoghurt with the method used by is: methoddemonstrate, and question and answer; and third conductthe evaluation fromcondition of citizen of pasca training and the increasing of skilled ofcompetitor.Result of training activity assessed enough succeed because citizencan mengolah of product of olahan milk become the industrial productolahan home. All competitor give the positive respon and antusiasme, thismatter is shown by their attendance during execution take place andfollowed by 48 competitor from citizen.Keywords: Cheese, Yoghurt, lactic acid bacteria